Performance of controlled low-strength material containing fly ash and waste paper sludge ash as ground backfilling material / Mohd Azrizal Fauzi - Fauzi, Mohd Azrizal (2024)
Amidst mounting pressure on the cement and concrete industries to adopt environmentally sustainable practices, addressing the sustainability challenges associated with ground backfilling, particularly employing controlled low-strength materials (CLSM), becomes imperative. Despite the promising potential of integrating industrial by-product wastes such as fly ash (FA) and waste paper sludge ash (WPSA) as supplementary cementitious materials (SCM) in CLSM, a significant gap persists in the availability of comprehensive guidelines for formulating mixtures with these nonconventional materials, hindering widespread adoption. To tackle this challenge, this research leverages statistical experimental design techniques to optimise CLSM formulations using solely industrial by-product waste resources systematically. Investigating the properties and environmental impact performances of these optimised mixtures, the study employed a response surface method to examine the influence of key parameters on CLSM properties. Four (4) phases were undertaken: mix design, analysis of key parameters, optimisation and validation, and evaluation of optimised CLSM backfill. Statistical models were developed in the mix design phase to evaluate fresh and hardened properties considering three (3) key parameters: water-cementitious material (w/cm) ratio, SCM percentage (ranging from 50% to 100% of total cementitious materials), and total cementitious materials content. Subsequent analysis revealed the impact of these parameters on properties such as flowability, bleeding, segregation, initial stiffening time, and densities (fresh, air-dried, oven-dried), among others. Optimised statistical models identified an optimal w/cm ratio of 2.53 for balanced flowability and segregation resistance, while a total cementitious materials content of 200 kg/m³ enhanced segregation resistance and fluidity. Increased FA% and WPSA% levels notably improved flowability, with FA-CLSM showing enhanced flowability at higher FA percentages. Notably, FA-CLSM achieved an Unconfined Compressive Strength (UCS) of 3131.02 kPa at a 2.53 w/cm ratio, surpassing WPSACLSM mixtures. Environmental assessments revealed leachate concentrations of heavy metals well below regulatory limits, ensuring non-hazardous disposal of CLSM mixtures. Validated statistical models offer guidance for efficient mix design processes, underscoring the significance of tailored CLSM formulations for enhancing performance and sustainability in construction practices.